2014
DOI: 10.1136/bcr-2014-206983
|View full text |Cite
|
Sign up to set email alerts
|

Severe Langerhans cell histiocytosis in an infant: haemophagocytic syndrome association

Abstract: Langerhans cell histiocytosis (LCH) is a rare disease of unknown origin with a heterogeneous clinical presentation, varying from benign and self-limited to lethal. It is classified as single or multisystemic, according to the number of organs involved (one or at least two, respectively). Diagnosis can be challenging and is based on the histological and immunophenotypic examination of affected tissues. Secondary haemophagocytic lymphohistiocytosis is rarely reported in association with LCH and may impair its di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…17,18 Although to the best of our knowledge the underlying etiology of malignancy-associated HLH remains poorly understood, it is proposed that malignant as well as infiltrating immune cells promote inflammation by secreting cytokines, such as interferon γ, which is capable of driving the activation of macrophages and T cells. [3][4][5][6][7][8][9][10] In what to our knowledge is the largest study to date, 30 patients were included but the study focused primarily on pathology with little information provided regarding confirmatory testing for HLH, treatment, and outcome. 22,23 Collectively, these cytokines amplify a local as well as systemic cytokine cascade, supporting the belief that LCH itself may be capable of inducing an HLH-like hyperinflammation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Although to the best of our knowledge the underlying etiology of malignancy-associated HLH remains poorly understood, it is proposed that malignant as well as infiltrating immune cells promote inflammation by secreting cytokines, such as interferon γ, which is capable of driving the activation of macrophages and T cells. [3][4][5][6][7][8][9][10] In what to our knowledge is the largest study to date, 30 patients were included but the study focused primarily on pathology with little information provided regarding confirmatory testing for HLH, treatment, and outcome. 22,23 Collectively, these cytokines amplify a local as well as systemic cytokine cascade, supporting the belief that LCH itself may be capable of inducing an HLH-like hyperinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…LCH can affect patients of all ages and is associated with a broad spectrum of clinical manifestations and outcomes. 1,2 Occasionally, patients with multisystem LCH (MS-LCH; ie, LCH involving ≥2 organ systems) develop severe inflammation resembling that observed in patients with hemophagocytic lymphohistiocytosis (HLH), [3][4][5][6][7][8][9][10] a heterogeneous group of disorders typified by excessive activation of the immune system. 11 HLH can be primary Cancer March 15, 2019 (ie, hereditary) or secondary (ie, nonhereditary) in origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the majority of studies were case reports or small series studies. [ 9 11 ] So far, the study with largest patient cohort regarding the interrelationship between childhood LCH and HLH showed that a tentative diagnosis of HLH could be made in 12 out of 30 cases (40%) of childhood LCH, with 7 cases (23.3%) fully fulfilling the clinical diagnostic criteria of HLH. The authors speculated that cytokines produced by activated cytotoxic T lymphocytes or CD1a positive histiocytes might be the underlying mechanism of macrophage activation and resultant HLH.…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, some children may experience significant morbidity such as diabetes insipidus (DI), anterior pituitary dysfunction, 6 and end-stage liver disease. 7 A rare but potentially fatal complication of systemic LCH is secondary hemophagocytic lymphohistiocytosis (HLH), [8][9][10] which has been shown to occur in children with multisystem LCH with a cumulative incidence of 9.3%. 10 Primary HLH arises from cytotoxic T-cell and macrophage hyperactivation because of deficiencies in normal negative regulatory signaling, whereas secondary HLH reflects massive immune system activation in response to an insult such as infection or malignancy.…”
Section: Introductionmentioning
confidence: 99%